Improving the Pelvic Exam Experience: A Human-Centered Design Study. (28th July 2017) - Taylor, Gina A; McDonagh, Deana; Hansen, Michael J
Abstract: Many women are traumatized by pelvic examinations, causing them to experience increased anxiety or avoid these exams completely. Use of a vaginal speculum is necessary during the majority of pelvic examinations. The traditional speculum design is uncomfortable for most patients and lacks considerations for the health care provider. Incorporating Human-Centered Design methodology into the resolution of this problem allows for the consideration of the patient and doctor experiences when making design decisions. Interviews and observation can provide valuable insight for improvements to the design and user experience. Through empathic design, it is possible to develop an instrument that is functional and ergonomic for the health care provider while also promoting the physical and emotional comfort of the patient being examined. This paper challenges current medical standards and provides a novel approach to pelvic examination using a new vaginal speculum.